Winter-time Hydraulic Jump over the Pokhara Valley, Nepal - Shrestha, S.; Regmi, R. P. (Journal of Nepal Physical Society, 2023)
The Pokhara Valley is set to be one of the aviation hubs of Nepal with the opening of an international airport. The complex mid-hill mountainous topography of the Gangi-Himalaya and the characteristic wind system of the valley make safe aviation rather challenging over the valley. This study using the Weather Research and Forecasting modeling system shows that hydraulic jump-like phenomena occur regularly during winter in the western and central part of the Pokhara Valley during late afternoon/early evening when the airport may remain relatively busy. The jump occurs over the western part of the valley when the regional southwesterly plain to mountain wind via the Putalibazar Valley intrudes into the Valley crossing the Deurali-Mattikhan hill. The jump-like flow is accompanied by the formation of a mild reverse roller above the jump region and the head-on convergence with the northeasterly katabatic/drainage wind from Parche-Namarjung along the southeast–northwest oriented valley axis generating an updraft of as much as 0.4 to 0.8 m s-1. The southwesterly overrides northeasterly generating clockwise vertical rotors and high turbulence over the northeastern region of the valley. An early prediction of possible wind hazards at high spatiotemporal resolutions are highly desired to make aviation activities in the region safer for civil aviation.